The 2011 health analysis in Mataram City: application of the Bryant Method - Aini Khulaila; Made Utama; Anak Agung Sagung Sawitri (Universitas Udayana, 2013)
The budget for health program of Mataram City is only allocated IDR 39,868,095,387 or 3.9% of the total annual city budget. It is lower than minimum 5% proportion as required by the government regulation. This study involved assessing the priority areas in health according to implicated stakeholders from the health office (head of communicable diseases control, family health, living environments, immunisations and surveillance staff). Data was collected through the months of January-July 2012 through self administered questionnaire using the Bryant Method. Secondary data (census, economic, socio-cultural and health records as well as population income levels) was obtained through government records. Data was analysed and interpreted in order to gain insight into perceived priority areas. Cross checking of respondent input was conducted to validate data. Results indicated that the priority health issues are: dengue fever, HIV/AIDS, TB, respiratory infections, hypertension, diarrhea and traffic accidents. Obstacles experienced during fieldwork included time restraints from respondents and inconsistencies within secondary data. The absence of the key persons in several discussions and unavailability of written data and reports are the main challenges during investigation. Improving the quality of program data findings and taking the beneficiary of the data source are suggested. Future recommendations include further more qualitative research into the issue, increased collaboration and cooperation between implicated stakeholders as well as more conscientious keeping of public records.